2017
DOI: 10.1038/gim.2016.107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing and genetic counseling for amyotrophic lateral sclerosis: an update for clinicians

Abstract: Patients with amyotrophic lateral sclerosis (ALS) often have questions about why they developed the disease and the likelihood that family members will also be affected. In recent years, providing answers to these questions has become more complex with the identification of multiple novel genes, the newly recognized etiologic link between ALS and frontotemporal dementia (FTD), and the increased availability of commercial genetic testing. A genetic diagnosis is particularly important to establish in the era of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 74 publications
0
83
0
8
Order By: Relevance
“…Any human population sample, whether an ALS cohort (Cirulli et al 2015;Ozoguz et al 2015) or other disease cohort (Lek et al 2016), carry many rare genetic variants. If not efficiently examined, this heterogeneity can increase the difficulty and cost of genetic diagnosis, which remains a key barrier for implementation in the clinical setting (Roggenbuck et al 2016). The use of single variant tests in clinical diagnostic laboratories is limited for ALS given the breadth of diseasecausing variants that have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Any human population sample, whether an ALS cohort (Cirulli et al 2015;Ozoguz et al 2015) or other disease cohort (Lek et al 2016), carry many rare genetic variants. If not efficiently examined, this heterogeneity can increase the difficulty and cost of genetic diagnosis, which remains a key barrier for implementation in the clinical setting (Roggenbuck et al 2016). The use of single variant tests in clinical diagnostic laboratories is limited for ALS given the breadth of diseasecausing variants that have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of multiple novel genes in ALS and the newly recognized link between ALS and frontotemporal dementia have resulted in the need to incorporate genetic counseling into multidisciplinary ALS care 16,90,91…”
Section: Introductionmentioning
confidence: 99%
“…The C9orf72 repeat expansion is the most common genetic cause of MND. This is reported to account for about 40% of familial and about 7% of sporadic disease, 31 , 32 but the exact frequency of MND‐related genes varies between different populations and specific data on prevalence in Australia are still limited. Preliminary national studies identified C9ORF72 mutation in 38.5% of familial cases and 3.5% of sporadic cases 33 .…”
Section: Genetics: New Insightsmentioning
confidence: 99%
“…Preliminary national studies identified C9ORF72 mutation in 38.5% of familial cases and 3.5% of sporadic cases 33 . There are also some shared clinical traits in these patients, who are typically of northern European descent and who clinically often have neuropsychiatric symptoms, including frank FTD 32 , 33 . There is also a suggestion of higher frequency of bulbar‐onset disease, earlier age of symptom onset, and more rapid disease progression 26 , 32 …”
Section: Genetics: New Insightsmentioning
confidence: 99%
See 1 more Smart Citation